The More Rural the Less Educated? An Analysis of National Policy Strategies for Enhancing Young Adults’ Participation in Formal and Informal Training in European Rural Areas - Julia Weiss; Christin Heinz-Fischer (Youth, 2022)
Young adults in rural areas in many cases have limited educational opportunities. To obtain higher educational qualifications, rural youth often travel long distances. Therefore, many rural youths choose the “shorter” route and complete vocational training closer to home or drop out of their education prematurely. Against this background, this study examines the education policies of European countries and explores the extent to which these problems are addressed within their policy framework and what measures are taken to improve the situation. Using a unique dataset of policies of 31 European countries for the period 2010 to 2020, we examine more than 500 national and subnational policies that address formal and informal education and training. The results show that despite the sometimes high number of rural youths not in education, employment, or training (NEETs) and high early-school-leaving rates, only some countries have developed a respective policy strategy. The analysis presents the different measures implemented in the countries and furthermore shows that a high problem pressure in a country is not necessarily accompanied by a consideration in policy. Prospectively, there is a need for new policies that understand the multidimensionality of the issue and significantly improve the situation of rural youth.